2011
DOI: 10.1055/s-0031-1297042
|View full text |Cite
|
Sign up to set email alerts
|

General Pharmacology of KP-102 (GHRP-2), a Potent Growth Hormone-Releasing Peptide

Abstract: The general pharmacological effects of the hexapeptide KP-102 (D-alanyl-3-(2-naphthyl)-D-alanyl-L-alanyl-L-tryptophyl-D-phenylalanyl-L-lysinamide dihydrochloride, growth hormone-releasing peptide-2, GHRP-2, pralmorelin, CAS 158861-67-7), which potently promotes growth hormone (GH) release by acting at both hypothalamic and pituitary sites, were evaluated in various animal experimental models. The administration of KP-102 showed no obvious effect at a pharmacological dose on the central nervous system. KP-102 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Although more detailed studies are needed to define the appropriate dose of GHRP-2, Furuta et al reported that GHRP-2 has no serious side-effects at dose levels that induce GH-releasing activity. 21 …”
Section: Effects Of Ghrp-2 On Systemic and Myocardial Growthmentioning
confidence: 99%
“…Although more detailed studies are needed to define the appropriate dose of GHRP-2, Furuta et al reported that GHRP-2 has no serious side-effects at dose levels that induce GH-releasing activity. 21 …”
Section: Effects Of Ghrp-2 On Systemic and Myocardial Growthmentioning
confidence: 99%
“…the reason for this may be that GhRp-2 might have a different effect on AVp secretion independent of osmolality and hemodynamic factors, unlike ghrelin, probably because GhRp-2 is an exogenous ligand that binds the GhS receptor, while ghrelin is an endogenous ligand that binds the GhS receptor [2]. this difference supports the notion that, for Acth secretion, GhRp-2 acts via cRF [7], while ghrelin acts via AVp [12], and ghrelin stimulates secretion of gastric juice with gastrin, whereas GhRp-2 has no such effects [23]. Moreover, AVp levels increase significantly with the itt [17][18][19].…”
Section: Discussionmentioning
confidence: 54%
“…Although pralmorelin reached Phase II clinical trials for the treatment of short statue, further development was discontinued. This was presumably because pralmorelin failed to increase plasma GH levels sufficiently in patients with GHD …”
Section: Results Of Major Clinical Trials and Current Statusmentioning
confidence: 99%
“…Pralmorelin, also known as GHRP2, is an orally active, short‐acting, synthetic peptide that was originally developed by Polygen in Germany and Tulane University in the USA and then acquired by Kaken Pharmaceutical Company in Japan . In rats, pralmorelin was associated with two‐fold to three‐fold increase in GH release compared with GHRP6 after intravenous administration.…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation